Jeunes et imaginaire de la modernité à Abidjan - Bahi, Aghi (2011)
What is modernity for the youngsters in Abidjan today, in the era of globalization? What are the loci of this modernity and how do they express it? How do these abidjanian youngsters construct themselves as modern beings (individuals)? The relation of the youngsters to modernity is considered as the daily (re)constructed consequence of their ordinary actions. Based on individual interviews and regarding the results of previous studies, this paper examines ordinary and routine social practices so‑called modern by the young themselves in order to grab their understanding of modernity. It appears that the common linguistic expressions and the daily practices of the young abidjanese are creative of an imaginary of modernity.